Nrf2 in ischemic neurons promotes retinal vascular regeneration through regulation of semaphorin 6A - Wei, Yanhong (Proc Natl Acad Sci U S A, 2015)
Delayed revascularization of ischemic neural tissue is a major impediment to preservation of function in central nervous system (CNS) diseases including stroke and ischemic retinopathies. Therapeutic strategies allowing rapid revascularization are greatly needed to reduce ischemia-induced cellular damage and suppress harmful pathologic neovascularization. However, key mechanisms governing vascular recovery in ischemic CNS, including regulatory molecules governing the transition from tissue injury to tissue repair, are largely unknown. NF-E2-related factor 2 (Nrf2) is a major stress-response transcription factor well known for its cell-intrinsic cytoprotective function. However, its role in cell–cell crosstalk is less appreciated. Here we report that Nrf2 is highly activated in ischemic retina and promotes revascularization by modulating neurons in their paracrine regulation of endothelial cells. Global Nrf2 deficiency strongly suppresses retinal revascularization and increases pathologic neovascularization in a mouse model of ischemic retinopathy. Conditional knockout studies demonstrate a major role for neuronal Nrf2 in vascular regrowth into avascular retina. Deletion of neuronal Nrf2 results in semaphorin 6A (Sema6A) induction in hypoxic/ischemic retinal ganglion cells in a hypoxia-inducible factor-1 alpha (HIF-1α)-dependent fashion. Sema6A expression increases in avascular inner retina and colocalizes with Nrf2 in human fetal eyes. Extracellular Sema6A leads to dose-dependent suppression of the migratory phenotype of endothelial cells through activation of Notch signaling. Lentiviral-mediated delivery of Sema6A small hairpin RNA (shRNA) abrogates the defective retinal revascularization in Nrf2-deficient mice. Importantly, pharmacologic Nrf2 activation promotes reparative angiogenesis and suppresses pathologic neovascularization. Our findings reveal a unique function of Nrf2 in reprogramming ischemic tissue toward neurovascular repair via Sema6A regulation, providing a potential therapeutic strategy for ischemic retinal and CNS diseases.